Comparison of adults and children anthropometric tables: mass segment distribution - Otmani, S.; Marchitto, M.; Michon, G.; Watier, B. (Computer methods in biomechanics and biomedical engineering, 2020)
Body Segment Inertia Parameters (BSIP) and particularly masses of the segments are essential to compute accurate kinetics parameters and provide inverse dynamics process or balance analysis during gait. One of the most common methods to obtain BSIP is to use regression equations obtained from anthropometric analysis of medical imaging, measurements on living subjects or of human cadavers (Dempster 1955; Clauser 1969; Zatsiorsky et al. 1990; Dumas and Wojtusch 2018) based on the total mass of the subjects.Due to dissimilarities in the experiments and data processing, data from different studies cannot be pooled and few anthropometric tables present complete data with accurate definition of the BSIP for children. Particularly a lack of knowledge regarding limits of the segments, definition of local frame, products of inertia are observed in the previous researches. Moreover, limited information is available regarding BSIP for children as most of the anthropometric tables were based on adults over 18-year old.Thus, a question remains regarding the use of adult’s regression equations in order to define BSIP parameters for children.This study aims at comparing the segments’ mass distribution of children from 4- to 15-year old between anthropometric tables based on adult’s data (Dempster 1955; Clauser 1969; Zatsiorsky et al. 1990; Dumas and Wojtusch 2018) and those based on children data (Jensen 1986) considered as reference. This last anthropometric table only has the specificity to include the age in the regression equations from 4 to 15 years. This comparison could help researchers to know if an anthropometric table based on adult’s data can be used to determine the BSIP of healthy or pathologic child.